5(x-1)-11=-1

Simple and best practice solution for 5(x-1)-11=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)-11=-1 equation:


Simplifying
5(x + -1) + -11 = -1

Reorder the terms:
5(-1 + x) + -11 = -1
(-1 * 5 + x * 5) + -11 = -1
(-5 + 5x) + -11 = -1

Reorder the terms:
-5 + -11 + 5x = -1

Combine like terms: -5 + -11 = -16
-16 + 5x = -1

Solving
-16 + 5x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 5x = -1 + 16

Combine like terms: -16 + 16 = 0
0 + 5x = -1 + 16
5x = -1 + 16

Combine like terms: -1 + 16 = 15
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| 256=5-u | | 2/3×2/3×2/3×2/3 | | 2y-2=22-2 | | V=6hx^2 | | 3(x-4)-13=-16 | | -8+9k=28 | | 49=4v-15 | | 1/3(3x-15)=-7 | | 2(x-1)-16=-28 | | 4x+2(x+3)=3(c-1) | | (x/5-2=-27 | | 5(5x+3)=65 | | 4x+4+2x+6=6x+15 | | -2(4b+4+6b)+3(7-5b)= | | 5u-14=76 | | 2xsquared-20=0 | | 4(x-3)=2x-11 | | 6+8x=10x-4 | | 9n+9=54 | | 6x-54=24 | | x-3x+7=0 | | -1/4x=3 | | 13-8v=5v-5 | | 3x-2y+6-6x+5y-8= | | 11x+2=5x+2 | | 16-(-82)= | | 6y+5y+4x+2y-x= | | x+0.02=3.5 | | -4x-47=0 | | 2s+14-s=1 | | w-7=8 | | -57-12x=-19x+6 |

Equations solver categories